Analisis Time Series Perencanaan Inventory Naphtha dan Penentuan Reorder Point pada Crude C4 - Kuncoro, Kefin Rendi; Ramayanti, Gina; Rosihin, Rosihin (Universitas Serang Raya, 2016)
The raw material used by this company is the result of refining petroleum in the form of naphtha and crude c4. In this discussion, there was often a buildup of ships in the Anchorage area before leaning on the Jetty because there was no ready storage of raw materials to receive cargo. To overcome the problem in inventory naphtha, it uses the exponential smoothing method by finding the smallest MAD. And to overcome the difficulty in C4 crude using the reorder point method to determine the existing safety stock. Based on the results of calculations using the exponential smoothing method, the smallest MAD is obtained which is 5099.66 with a value of Î± 0.9. And with the estimate of safety stock for naphtha tanks that is equal to 11898.5 tons with a safety factor of 95%. The results of the reorder point calculation on Crude C4 obtained a safety stock of 1959 Tons with ROP (Reorder Point) of 3959 Tons which means that when supplies have reached ROP, it is recommended to send the Crude C4 product to the shipment so that excessive production does not accumulate in the tank.